Implementasi Rencana Penyediaan Ruang Terbuka Hijau untuk Mewujudkan Kota Bandar Lampung menuju Smart City - Zhahira Rhamadan; Citra Persada; Arie Fitria; Muhammad Irfan Affandi; Firda Sari (Jurnal Kajian dan Penelitian Umum, 2026)
The provision of green open spaces (GOS) is an important aspect of achieving sustainable urban development and supporting the smart environment dimension of the smart city concept. However, the implementation of green open space planning in Bandar Lampung City still faces various challenges, as reflected in the low percentage of GOS area that has not yet met the minimum requirement of 30 percent mandated by national regulations. This study aims to analyze the implementation of green open space planning in Bandar Lampung City in supporting smart city development, identify factors influencing policy implementation, and determine priority factors affecting GOS implementation. Data were collected through in-depth interviews, observation, documentation studies, and questionnaires based on the Analytical Hierarchy Process (AHP). Data were analyzed using the Miles and Huberman interactive model and AHP with Expert Choice software. The results indicate that GOS implementation remains suboptimal due to limited government commitment, land and budget constraints, weak inter-agency coordination, and insufficient stakeholder involvement. AHP results show that disposition is the most influential factor (0.484), followed by resources (0.320), communication (0.132), and bureaucratic structure (0.064). Strengthening government commitment, budget support, land utilization, and stakeholder collaboration is essential for sustainable GOS implementation and smart city development in Bandar Lampung.